Cyberloafing: Minimalizing Work Stress on Millennial Generations Employee - Dita Nurhidayah; Caecilia Tri Wahyanti (International Journal of Social Science and Business, 2021)
In the era of industry 4.0, technological changes are accelerating rapidly. Internet technology provides many conveniences for employees to deal with their duties. The use of the internet that has become a characteristic of individuals, especially employees, has a negative or positive impact. This study aims to determine the factors that cause cyberloafing behavior in millennial employees, how the impact of cyberloafing behavior, what kind of work stress experienced by millennials and how cyberloafing behavior can minimize work stress in millennial generations. The research method applied is descriptive method with a qualitative approach. The data collection technique used is by conducting interviews with 2 millennial generation employees and 1 leader. The interview technique is done in semi-structured technique and list of questions are prepared for the interview which are developed based on the relevant literature. After the data is obtained, the presentation and data reduction are carried out, then conclusion is drawn. The result of this study indicates that cyberloafing behavior in millennial generation employees is an activity carried out by millennial generation employees to minimize work stress occurred during working hours in the company environment. This means that cyberloafing behavior among millennial generation employees is considered an activity that can refresh brain performance. This behavior is carried out to reduce or minimize the stress experienced such as entertainment when stressed, refreshing the brain from stress and boredom because they have to work continuously.